ANALISIS TATA CARA PELAKSANAAN UANG PAKSA DAN SANKSI ADMINISTRATIF DI PENGADILAN TATA USAHA NEGARA - Rika Afriza; Mexsasai Indra; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Indonesia is a country that is based on state law. Then surely the actions of the government should be based on the applicable law. Principles of the State Administration of justice, to put the judicial control in the implementation of good governance a bias in the state system of Indonesia. Where a State Administrative Court's decision does not have the power eksekutorial, how could the law and the public can supervise the government that carried out by officials of the Administration Negara.maka required an ordinance implementing the forced money and administrative sanctions tegasa that the decision of Justice State Administration can be executed properly. The purpose of this thesis is to find an idea about the procedures of money forced and administrative sanctions in the State Administrative Court.This type of research is research with normative juridical approach, yatu approach is to discuss the principles of law. This research was conducted by examining the library materials or secondary data such as legislation and books written by lawyers. Source data used are primary data source, secondary data sources, and tertiary data sources. Data pengupulan technique is the method of literature study.The conclusion is the first forceful measures as mandated in Article 116 of Law No. 51 of 2009 has yet to be implemented effectively related to the absence of implementing regulations regarding the forced currency and the administrative sanctions. Both for the payment of money shall be drawn from the paka personal finances because yangbersangkutan officials had deliberately not implementing the court ruling. In the case of the imposition of administrative sanctions, types of penalties can be adjusted by judges with huge losses suffered by the plaintiffs for not implementation of the court ruling.Advice authors to the problems studied were first need uniform laws to formulate the idea of the researchers stated in the form of government regulation that material containing cargo the ordinance. Both the State Administrative Court (Chief Justice) need to be proactive in monitoring the implementation of court decisions that have permanent legal force. Third parties especially active berpertisipasi plaintiffs judged necessary to provide information on whether a decision has force of the law have been implemented or not.Keywords; Forced money - administrative sanctions - PTUN